S152 Dexamethasone reverses established monocrotaline-induced pulmonary hypertension in rats and increases pulmonary BMPR2 expression. (16th November 2010) - Price, L C; Wort, S J; Montani, D; Tcherakian, C; Dorfmuller, P; Souza, R; Shao, D; Simonneau, G; Howard, L S; Adcock, I; Humbert, M; Perros, F
Abstract : Background: Pulmonary arterial hypertension (PAH) is associated with pulmonary vascular inflammation and dysregulated bone morphogenetic protein receptor type 2 (BMPR2) signalling in both human and experimental PAH. We evaluated the effects of dexamethasone on established monocrotaline-induced PAH in rats for potential reversal of PAH, at time points when pulmonary vascular remodelling has already developed (from day 14 after a single injection of monocrotaline at day 0), and for the effects on pulmonary IL6 and BMPR2 expression. Methods: Saline-treated controls, monocrotaline-exposed, monocrotaline-exposed and dexamethasone-treated rats (5 mg/kg/day, 1.25 mg/kg and 2.5 mg/kg/48 h given from day 14–28 and day 21–35) were evaluated at day 28 and day 35 following monocrotaline for pulmonary vascular haemodynamic parameters, right ventricular hypertrophy, morphometry, immunohistochemistry, whole lung IL-6 and BMPR2 expression by quantitative real-time PCR (qRT-PCR). Results: Dexamethasone significantly improved pulmonary haemodynamics and morphometric indices of pulmonary vascular remodelling, reversing PAH when given at day 14–28, day 21–35 following monocrotaline, as well as improving survival in monocrotaline-exposed rats compared to controls (log rank p<0.0001). Dexamethasone reduced both monocrotaline-induced whole lung IL-6 overexpression (p<0.05), as well as reducing IL-6-expressing adventitial inflammatory cell infiltration as assessed by immunohistochemistry. This was associated with pulmonary BMPR2 down-regulation (p<0.01) following monocrotaline, which was significantly increased following day 14–28 dexamethasone treatment in whole lung (p<0.05) (Abstract S152 Figure 1 ). Cellular BMPR2 was also increased following in vitro treatment of control pulmonary artery smooth muscle cells (PASMC) with ×10 −8 molar dexamethasone (p<0.05), but not in PASMC isolated from pulmonary hypertensive rats. Dexamethasone (×10 −8 and 10 −7 molar) also reduced proliferation of PASMC isolated from both control and pulmonary hypertensive rats (p<0.05 for both doses). Conclusion: PAH in this well-characterised experimental model can be reversed by dexamethasone, and survival is improved. In this model, mechanisms may involve reduction of IL-6-expressing inflammatory cells, reduced proliferation of vascular smooth muscle cells, and restoration of pulmonary BMPR2 expression may be important.